Rancang Bangun Sistem Jaringan Nirkabel untuk Pemantauan Penggunaan Air Pelanggan PDAM - Sean Satya Henura; Triyogatama Wahyu Widodo (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2015)
This study builds system prototype to monitor customer’s usage of water provided by PDAM through wireless network. The system were made to help customers who don’t have access to their water usage history, preventing them to properly manage it. On a bigger scale, this system could be solution to the company problem on collecting their customer usage data which have to be done by visiting each customer’s house monthly.This system was made by attaching components to water meter that capable of sending meter data to a server to be saved on MySQL database. For usage monitoring, an app made for android smartphone that sends request to server asking for usage data of certain time wanted by the user was used. The data were sent using HTTP protocol on internet connectivity gained from Ethernet module on water meter part and either cellular connection or Wi-Fi on android smartphone part. Results gotten from the conducted tests show that functional-wise, the monitoring can be done accurately using 1.046 KBps bandwith during process. Of the 5 protocol tested, all proved to be working as designed. The tests show that data sending of water meter and data saving on server database are working.